2018
DOI: 10.1021/acs.joc.8b02062
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Templated Assembly of Cyclopropane-Fused Diazepanones and Diazecanones via exo-trig Nucleophilic Cyclization of Cyclopropenes with Tethered Carbamates

Abstract: A strain-release-driven, cation-templated nucleophilic 7-and 8-exotrig-cyclization of tethered Boc-protected amines to cyclopropenes is described. The featured reaction proceeds in diastereoand regioselective fashion and allows for preparation of the corresponding 2,5diazabicyclo[5.1.0]octan-6-ones and 2,6-diazabicyclo[6.1.0]nonan-7-ones as sole products in high yields. Preliminary studies on anticancer activities of these novel cyclopropane-fused medium heterocycles were performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…This process is supported by Nese and Aysen's work (Kaynak et al, 2018) that -COCl is a very reactive functional group and can easily be transformed to -COOR functionality with a lower energy barrier. By a quantitative analysis of the mechanism of acylation chlorination, it is found that the high energy barrier indicates the formation of -COCl may be related to the steric hindrance of substrates and the coordination effect of Fe atom (Cunico and Pandey, 2005; Maslivetc et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…This process is supported by Nese and Aysen's work (Kaynak et al, 2018) that -COCl is a very reactive functional group and can easily be transformed to -COOR functionality with a lower energy barrier. By a quantitative analysis of the mechanism of acylation chlorination, it is found that the high energy barrier indicates the formation of -COCl may be related to the steric hindrance of substrates and the coordination effect of Fe atom (Cunico and Pandey, 2005; Maslivetc et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, sulfonamides 8 were treated with freshly ground powdered KOH in anhydrous THF at 50 C, as these reaction conditions were previously shown to be optimal for the cyclization of carbamates. 30 Gratifyingly, most of sulfonamides tested (8a-f) underwent the reaction smoothly affording the corresponding products 9a-f in high yields. The reaction seems to be very tolerant to steric hindrance at the sulfonyl group.…”
Section: Resultsmentioning
confidence: 96%
“…These species could be accessed via the potassium-templated cyclization of cyclopropenes 6 with tethered carbamates (Scheme 1). 30 In order to carry out more focused and complete SAR studies, we wanted to gain access to analogs within scaffold 7 by replacing the Boc protecting group with a range of substituents. This study is focused on the synthesis of sulfonamides 9, which give rise to three points of diversity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our research group has extensive experience in controlling the chemo- and stereoselective assembly of medium-sized rings by employing the metal-templated addition of oxygen- , or nitrogen-based nucleophiles to functionalized cyclopropenes. We showed that this approach allowed for the highly efficient cyclization of 7- to 10-membered rings. We envisioned that a cyclopropene unit could also serve as a practical rigidified linchpin for a “click–click–cyclize” approach , to prepare medium-sized lactams via RCM. Herein we now disclose on the design and realization of this diversity-oriented synthetic strategy.…”
mentioning
confidence: 99%